Assessment of Southern Ocean mixed‐layer depths in CMIP5 models: Historical bias and forcing response. Issue 4 (9th April 2013) - Sallée, J.‐B.; Shuckburgh, E.; Bruneau, N.; Meijers, A. J. S.; Bracegirdle, T. J.; Wang, Z.
Abstract : [1] The development of the deep Southern Ocean winter mixed layer in the climate models participating in the fifth Coupled Models Intercomparison Project (CMIP5) is assessed. The deep winter convection regions are key to the ventilation of the ocean interior, and changes in their properties have been related to climate change in numerous studies. Their simulation in climate models is consistently too shallow, too light and shifted equatorward compared to observations. The shallow bias is mostly associated with an excess annual‐mean freshwater input at the sea surface that over‐stratifies the surface layer and prevents deep convection from developing in winter. In contrast, modeled future changes are mostly associated with a reduced heat loss in winter that leads to even shallower winter mixed layers. The mixed layers shallow most strongly in the Pacific basin under future scenarios, and this is associated with a reduction of the ventilated water volume in the interior. We find a strong state dependency for the future change of mixed‐layer depth, with larger future shallowing being simulated by models with larger historical mixed‐layer depths. Given that most models are biased shallow, we expect that most CMIP5 climate models might underestimate the future winter mixed‐layer shallowing, with important implications for the sequestration of heat, and gases such as carbon dioxide, and therefore for climate. Key Points: Deep winter mixed layer is consistently modeled too shallow and too light Excess air‐sea freshwater input over‐stratify the sea surface Future changes are associated with a strong state dependency